Placental chorioangiomatosis–a high risk pregnancy. Issue 715 (May 1985) - Jaffe, R.; Siegal, A.; Rat, L.; Bernheim, J.; Gruber, A.; Fejgin, M.
Abstract : A case of diffuse chorioangiomatosis leading to fetal hydrops, disseminated intravascular coagulopathy with massive umbilical vein thrombosis and fetal death is described. Although rare, this benign mesenchymatous malformation of the placenta should be kept in mind as a possible cause of neonatal morbidity. Prenatal diagnosis could prevent fetal death.